Pengembangan Buku Ajar Ushul Fiqh Al-Waraqat Kelas VII di MTS Ibrahimy Sukorejo Situbondo - Randi Suhendi; Abd Mughni (Program Pascasarjana Universitas Ibrahimy, 2018)
The textbook of ushul fiqh al-Waraqat was developed by following the steps of Borg and Gall. In the initial phase, the development was carried out at MTs Salafiyah Syafi'iyah through four stages, namely are needs analysis, Initial product design, Expert validation, and Revision. The advantage of this product development is that provides convenience to students by displaying many addition applicable examples; the updated form of printed textbooks, presentation of material, material content and concept map methods used to develop the textbook of ushul fikih al-Waraqāt. The limitations are the impact that can encourage students do not try and think hard to understand a complicated book; this textbook is still not entering the product testing phase to say it is ready to use.